Efektivitas Pembelajaran Berbasis Schoology - choirudin choirudin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2017)
Schoology E-learning as one of Learning Social Media (LSM). By using Schoology aims to show the effectiveness of Schoology E-learning through students' outcome in material quadratic equation. This is achieved when the students' learning outcomes were taught by Schoology E-learning can reach KKM, process skills and students' activities are better than conventional methods, process skills and students' activities get a positive effect on students' learning outcomes. The goal of this research is carried out research in MA Ma'arif Roudlotut Tholibin Metro from January to April 2015. The subjects were all students X MA Ma'arif Roudlotut Tholibin Metro. Researcher use cluster random sampling technique and selected XIPA1 as a class experiment consist of 20 students, XIPA2 as class control consist of 22 students and X IPS1 as a class test consist 23 students. The research instrument consisted of a test item subject matter of a quadratic equation and observation sheets on learning skill and student activities in learning. Test instrument used, validity, reliability, level of difficulty and different power. Analysis data consists of tests of normality, homogeneity, t-test and linear regression. The results were obtained on experimental class KKM, the KKM value 70 and the average grade 76,75 With the average value of these classes also proved that the experimental class average is better than the control class where control class average 70,23. Skills alias process positively to the learning outcomes of mathematics at 24,2%. Having an active students learn mathematics positive about the outcome of 19,8%. Process skills and students active learn mathematics positively to 25,7%.